Psychosocial beliefs of health providers' intention and behavior of offering HIV testing and counseling services: Estimating their relevance for intervention - Idris, Almutaz Mohammed; Crutzen, Rik; Van Den Borne, Hubertus W. (Frontiers in Public Health, 2022)
Background: Diagnosis of people with HIV is the first step to 95-95-95 global targets. The number of people with HIV in Sudan is low. This number can be increased by improving the provision of HIV Testing and Counseling (HTC) practices by healthcare providers (HCPs). This study aims to assess the psychosocial beliefs associated with HCPs’ behavior and intentions of offering HTC services and their relevance for intervention. Methods: This cross-sectional study was conducted in Kassala State, one of the eastern states of Sudan. From July 2019 to February 2020, 438 healthcare providers sampled from public health facilities completed a self-administered questionnaire. Data were analyzed using R software. Confidence Interval Based Estimation of Relevance (CIBER) was used to estimate the relevance of the beliefs to interventions. Results: The CIBER analysis showed that the belief "It causes many worries for patients if I offer or counsel them about HIV test" was negatively associated with HCPs’ intention and behavior to offer HTC services and a highly relevant belief for intervention. The belief "My manager thinks I should offer or counsel patients about HIV test" was positively associated with the behavior and intention to offer HTC services and was a relatively high relevant belief. The control belief“Patients are at low risk of HIV and do not need offering or counseling about HIV test” was negatively associated with both HCPs’ intention and behavior and was relevant to be selected in intervention. The control belief “If I offered or counseled patients about HIV test, I would spend more time with them" was negatively associated with the intention and behavior of HCPs towards HTC services, with high relevance to target with intervention. Conclusion: Different psychosocial beliefs among healthcare providers can influence their intention and behavior regarding offering HTC services to patients. More relevant beliefs are required to be targeted with interventions to promote both the intention and behavior of health care providers in providing HTC services to patients.